Preliminary results on novel adjuvant combinations suggest enhanced immunogenicity of whole inactivated pandemic influenza vaccines - Peletta, Allegra; Marmy, Aurélie; Guzelj, Samo; Ramos Barros, Alcidia; Jakopin, Žiga; Borchard, Gerrit (Frontiers in Drug Delivery, 2024)
Due to the inherent risk of a further pandemic influenza outbreak, there is a need and growing interest in investigating combinations of prophylactic vaccines and novel adjuvants, particularly to achieve antigen dose sparing and improved immunogenicity. Influenza is a highly variable virus, where the specific vaccine target is constantly changing, representing a major challenge to influenza vaccine development. Currently, commercial inactivated influenza vaccines have a poor CD8+ T response, which impacts cross-reactivity and the duration of response. Adjuvanted influenza vaccines can increase immune responses, thereby achieving better protection and cross-reactivity to help contain the spread of the disease. An early exploration of a hybrid cholesterol-PLGA nanoparticle delivery system containing the saponin tomatine and a NOD2 (nucleotide-binding oligomerization domain 2) agonist called SG101 was conducted. This combination was preliminarily evaluated for its ability to induce cellular immunity when combined with whole inactivated virus (WIV) influenza vaccine. After the adjuvants were manufactured using a single emulsion process, two formulations with different drug loadings were selected and physico-chemically characterized, showing sizes between 224 ± 32 and 309 ± 45 nm and different morphologies. After ensuring the lack of in vitro toxicity and hemolytic activity, a pilot in vivo assay evaluated the hybrid nanoparticle formulation for its ability to induce humoral and cellular immunity when combined with whole inactivated virus (WIV) H5N1 influenza vaccine by intramuscular administration in mice. Hemagglutinin inhibition (HAI) titers for adjuvanted groups showed no significant difference compared to the group vaccinated with the antigen alone. It was similar for CD4+ and CD8+ T cell responses, although the high drug loading formulation induced higher titers of IFNγ-positive CD8+ T cells. These proof-of-concept results encourage further investigations to develop the hybrid formulation with increased or different loading ratios, to investigate manufacturing optimization, and to evaluate the role of the individual immunostimulatory compounds in immune responses.